Longitudinal Study of Biosocial Factors Related to Crime and Delinquency, 1959-1962: (Pennsylvania) - Denno, Deborah W. ([Verlag nicht ermittelbar], 1988)
This study was designed to measure the effects of family background and developmental characteristics on school achievement and delinquency within a "high risk" sample of Black youths. The study includes variables describing the mother and the child. Mother-related variables assess prenatal health, pregnancy and delivery complications, and socioeconomic status. Child-related variables focus on the child at age 7 and include place in birth order, physical development, family constellation, socioeconomic status, verbal and spatial intelligence, and number of offenses.